DETERMINING THE FINANCIAL PERFORMANCE OF MALAYSIAN GREEN TECHNOLOGY COMPANIES USING TOBIN’S Q (Malaysian Management Journal, 2021)
Massive technology, business pressure and the growth of global market penetration have led to most businesses becoming more environmentally friendly. The issue of climate change, waste management, air pollution and water pollution have all challenged the practice of business ethics, notwithstanding the ever-present pressure for companies to be more competitive in the marketplace. To be more financially sustainable, most of the businesses are forced to keep the balance between resources available and future sustainability in the long-term period. To ensure the success of sustainability, green technology is one of the most important initiatives to motivate companies to become more financially sustainable in the future. Thus, the purpose of this study is to examine the factors that have influenced the financial performance of Malaysian green technology companies using Tobin's Q. The dependent variable is Tobin’s Q which represents the firm’s market value, while independent variables are measured by carbon productivity, waste productivity, energy productivity, growth and firm size. The data for the study came from 10 selected green technology companies listed in the Bursa Malaysia and were the top-ranked eco-friendly companies in Malaysia. The findings indicate that all independent variables (growth, carbon productivity, waste productivity and energy productivity) were significant, but firm size was not significant. The findings imply that by adapting to the use of green technology, companies benefited a lot in terms of minimizing cost, sustaining a healthy environment, as well as helping companies to become sustainable in the long term.